Enhanced corrosion resistance and cytocompatibility of biomimetic hyaluronic acid functionalised silane coating on AZ31 Mg alloy for orthopaedic applications. - Hoey, David; Agarwal, Sankalp; Morshed, Muhammad; Labour, Marie-Noelle; Duffy, Brendan; Curtin, James; Jaiswal, Swarna (My University, 2018)
This paper reports the corrosion resistant and cytocompatible properties of the hyaluronic acid-silane coating on AZ31 Mg alloy. In this study, the osteoinductive properties of high molecular weight hyaluronic acid (HA, 1–4 MDa) and the corrosion protection of silane coatings were incorporated as a composite coating on biodegradable AZ31 Mg alloy for orthopaedic applications. The multi-step fabrication of coatings first involved dip coating of a passivated AZ31 Mg alloy with a methyltriethoxysilane-tetraethoxysilane sol-gel to deposit a dense, cross-linked and corrosion resistant silane coating (AZ31-MT). The second step was to create an amine-functionalised surface by treating coated alloy with 3-aminopropyl-triethoxy silane (AZ31-MT-A) which facilitated the immobilisation of HA via EDC-NHS coupling reactions at two different concentrations i.e 1 mg.ml−1 (AZ31-MT-A-HA1) and 2 mg.ml−1 (AZ31-MT-A-HA2). These coatings were characterised by Fourier transform infrared spectroscopy, atomic force microscopy and static contact angle measurements which confirmed the successful assembly of the full coatings onto AZ31 Mg alloy. The influence of HA-silane coating on the corrosion of Mg alloy was investigated by electrical impedance spectroscopy and long-term immersion studies measurements in HEPES buffered DMEM. The results showed an enhanced corrosion resistance of HA functionalised silane coated AZ31 substrate over the uncoated equivalent alloy. Furthermore, the cytocompatibility of MC3T3-E1 osteoblasts was evaluated on HA-coated AZ31-MT-A substrates by live-dead staining, quantification of total cellular DNA content, scanning electron microscope and alkaline phosphatase activity. The results showed HA concentration-dependent improvement of osteoblast cellular response in terms of enhanced cell adhesion, proliferation and differentiation. These findings hold great promise in employing such biomimetic multifunctional coatings to improve the corrosion resistance and cytocompatibility of biodegradable Mg-based alloy for orthopaedic applications.
PUBLISHED
Keywords: Hylauronic acid; Orthopaedic applications; Coatings